La violencia de género En el ámbito laboral - Sánchez Trigueros, Carmen (Revista de Derecho, 2019)
Gender violence at work takes place in two different ways: sexual harassment andharassment based on gender. The latter is a phenomenon which has recently beenrecognized as such, and thus it has barely been studied as a discriminatory behavioror as a manifestation of gender violence at work. Everything that has been said up tothis point affects the Social Security sphere, on which the present study is focused.The reason why the Social Security sphere is the main focus of the study is due tothe doctrinal and judicial treatments that harassment at work (in any of its specificforms) has had since a contingency can be classified as an accident at work.
Keywords: Gender violence; female workers who are victims of sexist violence; Social Security; accident at work